Pathogen elimination and prevention within a regulated, Designated Pathogen Free, closed pig herd for long‐term breeding and production of xenotransplantation materials. (18th August 2018) - Noordergraaf, Jeske; Schucker, Adrienne; Martin, Mike; Schuurman, Henk‐jan; Ordway, Brianne; Cooley, Kevin; Sheffler, Marie; Theis, Kara; Armstrong, Chasa; Klein, Laura; Hansen, Doug; Olson, Megan; et al.
Abstract: Background: We established a Source Animal (barrier) Facility (SAF) for generating designated pathogen‐free (DPF) pigs to serve as donors of viable organs, tissues, or cells for xenotransplantation into clinical patients. This facility was populated with caesarian derived, colostrum deprived (CDCD) piglets, from sows of conventional‐specific (or specified) pathogen‐free (SPF) health status in six cohorts over a 10‐month period. In all cases, CDCD piglets fulfilled DPF status including negativity for porcine circovirus (PCV), a particularly environmentally robust and difficult to inactivate virus which at the time of SAF population was epidemic in the US commercial swine production industry. Two outbreaks of PCV infection were subsequently detected during sentinel testing. The first occurred several weeks after PCV‐negative animals were moved under quarantine from the nursery into an animal holding room. The apparent origin of PCV was newly installed stainless steel penning, which was not sufficiently degreased thereby protecting viral particles from disinfection. The second outbreak was apparently transmitted via employee activities in the Caesarian‐section suite adjacent to the barrier facility. In both cases, PCV was contained in the animal holding room where it was diagnosed making a complete facility depopulation‐repopulation unnecessary. Method: Infectious PCV was eliminated during both outbreaks by the following: euthanizing infected animals, disposing of all removable items from the affected animal holding room, extensive cleaning with detergents and degreasing agents, sterilization of equipment and rooms with chlorine dioxide, vaporized hydrogen peroxide, and potassium peroxymonosulfate, and for the second outbreak also glutaraldehyde/quaternary ammonium. Impact on other barrier animals throughout the process was monitored by frequent PCV diagnostic testing. Result: After close monitoring for 6 months indicating PCV absence from all rooms and animals, herd animals were removed from quarantine status. Conclusion: Ten years after PCV clearance following the second outbreak, due to strict adherence to biosecurity protocols and based on ongoing sentinel diagnostic monitoring (currently monthly), the herd remains DPF including PCV negative.